Analisis kebutuhan guru pendidikan jasmani, olahraga dan kesehatan pasca program guru pembelajar - Herka Maya Jatmika; Awan Hariono; Joko Purwanto; Caly Setiawan (Jurnal Pendidikan Jasmani Indonesia, 2017)
Penelitian ini bertujuan untuk memetakan kompetensi guru serta rumusan rekomendasi kebijakan yang mendalam dan kongkrit mengenai konsep strategi implementasi kerja yang efektif, efisien, produktif, kreatif dan inovatif demi terlaksananya program pembinaan kompetensi dan profesionalitas guru secara khusus di Daerah Istimewa Yogyakarta. Penelitian ini merupakan penelitian deskriptif kualitatif yang bersifat eksploratif reflektif. Subjek Penelitian adalah para guru PJOK di jenjang Sekolah Dasar di Yogyakarta sebanyak 30 guru yang dipilih melalui mekanisme purposive. Proses pengumpulan data akan dibantu dengan lembar-lembar identifikasi atau pencatatan. Mekanisme pengumpulan data yang selanjutnya adalah dengan melakukan FGD dengan beberapa guru yang juga ditentukan melalui mekanisme purposive. Sementara itu, langkah-langkah yang hendak diterapkan dalam metode analisis data berturut-turut berupa, (1) klasifikasi data; (2) display data; (3) melakukan  penafsiran dan interpretasi serta pengambilan kesimpulan. Guru PJOK di Daerah Istimewa Yogyakarta masih terkendala oleh kapasitas IT, kejelasan program Guru Pembelajar serta rendahnya pendampingan dari instansi terkait, sehingga dalam melaksanakan program ini mereka mengalamai stagnasi. Community based learning menjadi metode yang diingini oleh para guru PJOK dalam mengembangan kompetensinya. Konsep The Five Disciplines dari Peter Senge yang meliputi personal mastery, mental models, building shared vision, team learning, dan system thinking perlu didorong dalam upaya menghebatkan para guru PJOK. Needs analysis for the sport and health education teachers after the implementation of learning-teacher program AbstractThe study aims at mapping the in-depth and concrete teacher competence and recommendation formula toward the concept of effective, efficient, productive, creative and innovative job implementation in implementing the special program of teachers’ competence and professionalism development in the Province of Yogyakarta Special Region. The study is a qualitative descriptive research with explorative-reflective nature. When the study was conducted, the subjects were 30 teachers of Sports and Health Education in the Elementary Schools degree throughout the Province who had been selected by means of purposive sampling technique. Then, the data in the study were gathered bt means of identification or record sheets. After the data had been gathered, a focus group discussion (FGD) was conducted by involving several teachers who had also been selected by means of purposive sampling technique. Then, in analysing the data for the study the following procedures were applied: (1) data classification; (2) data display; (3) interpretation and conclusion drawing/verification. Based on the results of the study, it might be concluded that the teachers of Sports and Health Education in the Province of Yogyakarta Special Region are still troubled with their capacity of operating Information Technology, the clarity of Learning-Teacher Program and the low guidance provided by the relevant institution; as a result, the implementation of the program among the teachers become stagnant. The teachers in the program prefer Community-Based Learning as the method for the program implementation. In relation to the demand, the concept of Five Disciplines by Peter Senge that includes personal mastery, mental models, building shared vision, team learning and system thinking should be encouraged in empowering the teachers of Sports and Health Education.